Protection of the Environment through State Administrative Law - Sugiharto, Imawan; Hamzani, Achmad Irwan; Taufik, Moh.; Khamim, Mohamad; Aravik, Havis (International Journal of Criminology and Sociology, 2021)
The earth's water and the wealth contained in it are liquidated state to be utilized as much as the prosperity of the people. The state is here to manage nature by paying attention to the environment for the sustainability of development. Climate change, pollution, and environmental damage are threats. Research objectives for the role of the state as the executor of state administrative law, and analyze the basis of state administrative law enforcement in environmental management, as well as the role of the state in the management of natural resources that have an environmental impact. This research uses a normative approach, using secondary data and qualitative data analysis. The results showed that the role of the state as the executor of the duties of administrative law and protection of the environment is mentioned in the 1945 Constitution. The legal basis for enforcement of state administrative law is governed by the Environmental Law, the Energy Act, and the Mining, Minerals, and Coal Act. The function of the state through state administrative law in the management of environmentally impacted energy resources is covered by some of these laws.